Foreign Language Learning and Trade. Issue 2 (10th November 2016) - Ginsburgh, Victor; Melitz, Jacques; Toubal, Farid
Abstract: The paper is devoted to an econometric analysis of learning foreign languages in all parts of the world. Our sample covers 193 countries and 13 important languages. Four factors significantly explain learning: world population of speakers of home language, trade with speakers of foreign language, linguistic distance between home and foreign language and literacy. Trade may well deserve more emphasis than the other three factors, not only for its significance, but also because its direction can change faster and by a larger order of magnitude. Controlling for any of the 13 target languages, including English, is of no particular importance.